IgG4 serologic elevation in a patient with severe hidradenitis suppurativa: a case report and review of the literature - Gauger, Andrew J.; Fritz, Mike; Burgin, Callie B. (Frontiers in Medicine, 2024)
Hidradenitis suppurativa (HS) is a chronic cutaneous and systemic inflammatory condition. Increasingly, reports have found that immunoglobulins play a role in the exaggerated immune response occurring in severe HS. It is important to recognize these implications as HS patients may present with laboratory abnormalities relating to chronic inflammation and immune activation. If these laboratory abnormalities are mistakenly associated with another disease process, it could lead to invasive workup and treatment, causing harm to patients. We describe the case of a 23-year-old woman with Hurley stage III HS who was hospitalized and found to have persistent immunoglobulin-G4 (IgG4) elevation. Upon discharge, the patient was diagnosed with IgG4-related disease (IgG4-RD) and started treatment with azathioprine. However, the biopsy ultimately was negative for IgG4-RD, and she presented to our clinic several months later with worsening HS disease during an active flare. Physical examination revealed actively draining nodules and sinus tracts in the bilateral axillae, inguinal folds, and mons pubis region. A confusing laboratory marker with HS was observed in this case. IgG4 has the potential to inhibit or activate inflammation depending on the context, and so IgG4 elevation has been noted in varying disease states. IgG4 elevation is observed in chronic inflammatory states and may represent a compensatory response by the body. While no other cases have reported the association between HS and IgG4 elevation, IgG levels have been found to reflect HS disease severity. Therefore, IgG4 could play a potential role in HS disease monitoring, and awareness of this association is important for providers when managing patients with HS.